Analisis Dampak Intensif dan Disiplin Terhadap Prestasi Kerja Pegawai Kantor Kecamatan Jaya Kabupaten Aceh Jaya - Syarifuddin Syarifuddin; Bukhari Usman; Sulaiman Sulaiman; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research aims to determine the influence of work intensity and discipline on the performance of Jaya District office employees, Aceh Jaya Regency. The research methodology in this study is a complete survey/enumeration method, with a total sample and population of 32 employees of the Jaya District office, Aceh Jaya Regency. The analysis used was multiple linear analysis, data processing with the help of SPSS program analysis. The results of the research show that intensive and disciplinary variables influence the performance of employees at the sub-district office of Jaya District, Jaya Regency, simultaneously and partially.